Intracranial Hematoma and Abscess After Neuraxial Analgesia and Anesthesia: A Review of the Literature Describing 297 Cases. Issue 1 (March 2022) - Bos, E.M.; van der Lee, K.; Haumann, J.; de Quelerij, M.; Vandertop, W.P.; Kalkman, C.J.; Hollmann, M.W.; Lirk, P.
Abstract : ( Reg Anesth Pain Med . 2021;46:337–343. doi: 10.1136/rapm-2020-102154. Epub January 13, 2021) On occasion, neuraxial analgesia leads to severe complications and side effects such as intracranial hematoma or abscess. This study aimed to review literature cases describing intracranial hematomas or abscesses resulting from neuraxial block to analyze patient characteristics, management, and recovery to identify patients at increased risk and provide optimal care and improve outcomes.